DETERMINATION OF CONSECUTIVE REACTION RATE CONSTANTS BETWEEN GLYCINE AND ISOLEUCINE WITH o-PHTHALDIALDEHYDE AND 2-MERCAPTOETHANOL FROM SINGLE EXPERIMENT DATA - Iip Izul Falah; Triyono Triyono; Catur Atmaji (Indonesian Journal of Chemistry, 2011)
Kinetics study of chemical reaction is important in producing optimum product, designing a reactor, analyzing a compound, and many other purposes. This work presents the result of study of consecutive pseudo first order reaction between glycine and isoleucine with o-phthaldialdehyde and 2-mercaptoethanol in borate buffer solution at pH=9.0. Continuous detection was used to follow the change of fluorescence intensity of formed isoindole during the reaction. Although concentrations of initial compound and its derivative were not known; by using iteration method, the reaction constants could be determined with high precision from single experiment data. Result of the work showed that reaction rate constants k1 and k2 for consecutive reaction of glycine with excess of o-phthaldialdehyde and 2-mercaptoethanol were 18.75x10-3 and 26.70x10-5 s-1, respectively; whereas for isoleucine were 6.06x10-3 and 12.59x10-5 s-1, respectively.